Pengujian Game Berbasis Konten Budaya, Who is He: Let Me Out - Ervin Ahmad Nur Hidayanto; Muhammad Ilham Werdiansyah; Riwinoto Riwinoto; Waode Hafizah Ramadhani; Abdurrafi Naufal. S; Fadhli Yahya (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2022)
Games are one of the advances that are extremely mainstream with youngsters. The issue is, with the presence of games, youngsters and even grown-ups frequently abuse their time, so that games are made into something negative by society. Then again, Indonesian culture is currently progressively being abandoned, one of the variables is innovation like this game. The best arrangement is to join the two, by making an Indonesian cultural game, however education alone is not enough to attract the attention of gamers, since they are worried about ongoing interaction and game storyline, accordingly there should be a decent and designated bundling as a special attraction to players. An exceptional fascination for game players. Indonesian culture as far as understanding is exceptionally wide, relatively few people know about the ancient stories of society and unique things like shamans, the story can be utilized as a fascination for bundling the story in the game in light of the fact that so far there has been no Indonesian game that has taken Indonesian stories and pamali with great designs or appearance. 97% of gamers in Indonesia play games from abroad, this is very unfortunate because many foreign cultures enter through this platform. The research methods used in this research are quantitative. This game was tested on 100 gamer respondents at the Game Prime event in 2019. Based on the results of the questionnaire, it can be concluded that this game is quite interesting both in terms of graphics, mechanics, and cultural content. It will then be published on global platforms.